Rectal cancer developing from an anastomotic site 18 years after resection due to intussusception caused by Peutz-Jeghers polyposis in a 31-year-old man: a case report - Yuya Nobori; Takahiro Amano; Mieko Ochi; Toshio Kumasaka; Eiji Sunami (Surgical Case Reports, 2018)
Abstract Background Peutz-Jeghers syndrome (PJS) is an autosomal dominant disorder characterized by hamartomatous polyposis of the gastrointestinal tract. It is associated with a high risk of malignancy in the gastrointestinal tract, as well as in other organs. We report a case of colon cancer at the anastomotic site that occurred 18 years after high anterior resection of the rectum for intussusception caused by Peutz-Jeghers polyposis. Case presentation A 31-year-old man with PJS, who had undergone high anterior resection of the rectum for intussusception at the age of 12, presented to our hospital complaining of hematochezia. Colonoscopy revealed a hemorrhagic tumor protruding from the anastomotic site, which was histologically diagnosed as an adenocarcinoma. We performed a low anterior resection of the rectum including the anastomotic site, with combined resection of the strongly adherent ileum. Histological examination revealed that the adenocarcinoma had developed from the submucosal area, where the normal rectal mucosa had been incorporated into the stromal and bone tissues, resulting in heterotopic ossification in the anastomotic region. These findings suggested that the reconstructive surgical procedure or postoperative complications, such as anastomotic leakage, had formed the cavity where the cancer had developed. Conclusions We concluded that the cancer might be derived from the rectal mucosa with malignant potential that was present in the anastomotic region and exacerbated by the presence of chronic inflammation in the cavity after the patient’s initial operation.